Calidad de la energía eléctrica: diseño y construcción de un prototipo como alternativa para la monitorización de interrupciones y caídas de tensión (2005)
This article presents design and implementation of a prototype for recording interruptions and voltage sags which is intended as a low cost alternative in order to accomplish voltage waveform quality studies in distribution systems. This paper initially deals with some definitions related with power quality and then the prototype design and construction process is described in general terms. The achieved device consists of a data acquisition system and a graphical user interface which allows analyzing and specifying voltage levels for disturbance recording.